Juvenile justice staff endorsement of HIV/STI prevention, testing, and treatment linkage - Sheena K. Gardner; Katherine S. Elkington; Danica K. Knight; Sofia Huang; Ralph J. DiClemente; Anne C. Spaulding; Carrie B. Oser; Angela A. Robertson; Connie Baird-Thomas (BMC, 2019)
Abstract Background While involvement in the legal system offers an opportunity to educate, screen, and treat high-risk youth, research shows that staff attitudes toward these practices can serve as barriers to implementation. The current study investigates the degree to which JJ staff endorse HIV prevention, testing, and treatment linkage practices with youth under community supervision and examines differences between individuals who supervise youth (e.g., juvenile probation officer) and those working in non-supervisory roles (e.g., case manager, assessment specialist). Methods Juvenile justice staff consenting to participation in JJ-TRIALS completed an initial staff survey (N = 501). Survey items measured perceived importance of HIV/STI prevention (4 items); perceived importance of HIV/STI testing (7 items); and perceived importance of HIV/STI treatment linkage (8 items). Results Confirmatory Factor Analysis (CFA) was computed (SAS CALIS procedure) for each of the three domains. Findings suggest that while staff recognize that youth are at risk for HIV/STIs and require provision of HIV/STI prevention and treatment linkage, attitudes concerning the importance of procuring or providing testing services for youth is substantially lower. Furthermore, analytic models comparing staff with and without supervision responsibilities (computed using SAS PROC MIXED) indicated that attitudes differed by site and staff responsible for supervision rated HIV treatment linkage practices as less important compared to non-supervising staff. Conclusions Establishing partnerships with health agencies equipped with resources and skillsets to provide HIV/STI testing and related services may be an effective model to promote greater awareness and use of best practices among JJ staff and more effectively address the unmet needs of this high-risk population of youth.